INTEGRASI PENDIDIKAN ANTI-KORUPSI DALAM PEMBELAJARAN PAI: STUDI ANALISIS PERAN GURU SEBAGAI MOTIVATOR DAN EVALUATOR - Yunus Yunus; Endah Mawarny; Ma’fiyah Ma’fiyah (STKIP Pesisir Selatan, 2026)
This study aims to analyze the integration of anti-corruption education into Islamic Religious Education (PAI) learning at SMP 4 Malangke, Luwu Regency, and explore the role of teachers as motivators and evaluators in building student character. This research is motivated by the widespread integrity crisis and the tendency for PAI learning to remain textual-ritualistic, so that serious efforts are needed to internalize the values ​​of honesty (shiddiq) and trustworthiness into the school curriculum. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The results show that PAI teachers at SMP 4 Malangke have made integration efforts through careful planning using the value infusion method into the Lesson Implementation Plan (RPP) and linking religious material with the local wisdom of the Luwu community. As motivators, teachers have succeeded in raising students' intrinsic awareness through an exemplary approach (uswatun hasanah) and positive reinforcement. As evaluators, teachers apply authentic assessments based on behavioral observations to measure students' integrity in real terms. However, this study also identified several inhibiting factors, including the heavy administrative burden of assessments, biased student behavior at school, and the influence of an external environment that does not support integrity values.